2013
DOI: 10.1542/peds.2012-3773
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Breast Development in a Longitudinal Cohort

Abstract: BACKGROUND AND OBJECTIVES: There is growing evidence of pubertal maturation occurring at earlier ages, with many studies based on cross-sectional observations. This study examined age at onset of breast development (thelarche), and the impact of BMI and race/ethnicity, in the 3 puberty study sites of the Breast Cancer and the Environment Research Program, a prospective cohort of >1200 girls. METHODS: Girls, 6 to 8 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
234
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 294 publications
(257 citation statements)
references
References 42 publications
16
234
0
7
Order By: Relevance
“…Recently, Biro confirmed the important impact of BMI on breast development in girls in the USA (Biro et al, 2013). Taken together, those epidemiological studies point towards three windows of sensitivity for a link between energy availability/adiposity and pubertal development: prenatal life, early postnatal life and childhood.…”
Section: Critical Windows Of Exposure To Abnormal Energy Availabilitymentioning
confidence: 83%
“…Recently, Biro confirmed the important impact of BMI on breast development in girls in the USA (Biro et al, 2013). Taken together, those epidemiological studies point towards three windows of sensitivity for a link between energy availability/adiposity and pubertal development: prenatal life, early postnatal life and childhood.…”
Section: Critical Windows Of Exposure To Abnormal Energy Availabilitymentioning
confidence: 83%
“…74 Early signs of puberty manifest around the age of 10 years in girls (breast development) and 11.5 years in boys (testicular enlargement and spermarche-appearance of spermatozoa in first morning void). [75][76][77] Considerable interindividual variation in the timing of pubertal onset exists, ranging from 8 years to 13 years in girls and 9 years to 14 years in boys. 78,79 Subsequent hallmarks of puberty in boys include deepening of the voice and a growth spurt.…”
Section: Puberty and Reproductionmentioning
confidence: 99%
“…Several studies reported an association between overweight and early/precocious puberty (5, 33) suggesting the involvement of various environmental, genetic, and biochemical factors (5,7,17,34,35) to explain this association. However, what remains to be clarified is whether it is the high BMI that results in precocious pubertal development or is it the latter that promotes the weight gain (33,35).…”
Section: Bmi and Correlates Of Metabolic Syndromementioning
confidence: 99%
“…Females typically present with idiopathic forms, whereas in boys CPP is mostly due to organic lesions such as hypothalamic-pituitary congenital malformations, tumors, infections, infiltrative/inflammatory disorders, and iatrogenic or traumatic injuries (3). Genetic factors (mutations of KISS1, KISS1R, and MKRN3 genes (4)), secular trend, ethnicity, nutritional status, and environmental changes have all been involved in the pathogenesis of CPP (2,3,5), although their exact mechanisms of action remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%